Balance beam crossing times are slower after noise exposure in rats - Bartikofsky, Dylan; Hertz, Mikayla Jade; Bauer, David S.; Altschuler, Richard; King, W. Michael; Stewart, Courtney Elaine (Frontiers in Integrative Neuroscience, 2023)
Introduction The vestibular system integrates signals related to vision, head position, gravity, motion, and body position to provide stability during motion through the environment. Disruption in any of these systems can reduce agility and lead to changes in ability to safely navigate one’s environment. Causes of vestibular decline are diverse; however, excessive noise exposure can lead to otolith organ dysfunction. Specifically, 120 decibel (dB) sound pressure level (SPL) 1.5 kHz-centered 3-octave band noise (1.5 kHz 3OBN) causes peripheral vestibular dysfunction in rats, measured by vestibular short-latency evoked potential (VsEP) and reduced calretinin-immunolabeling of calyx-only afferent terminals in the striolar region of the saccule. The present study examined the functional impact of this noise exposure condition, examining changes in motor performance after noise exposure with a balance beam crossing task. Methods Balance beam crossing time in rats was assessed for 19 weeks before and 5 weeks after noise exposure. Balance beam crossings were scored to assess proficiency in the task. When animals were proficient, they received a single exposure to 120 dB SPL 3-octave band noise. Results During the initial training phase slower crossing times and higher scores, including multiple failures were observed. This was followed by a period of significant improvement leading to proficiency, characterized by fast and stable crossing times and consistently low scores. After noise exposure, crossing times were significantly elevated from baseline for 4-weeks. A total of 5 weeks after noise exposure, crossing times improved, and though still trending higher than baseline, they were no longer significantly different from baseline. Discussion These findings show that the noise-induced peripheral vestibular changes we previously observed at cellular and electro-physiological levels also have an impact at a functional level. It has been previously shown that imbalance is associated with slower walking speed in older adults and aged rats. These findings in noise-exposed rats may have implications for people who experience noisy environments and for seniors with a history of noise exposure who also experience balance disorders and may be at increased fall risk.